Patients with small prostates and low-grade intravesical prostatic protrusion – A urodynamic evaluation - Han Jie Lee; Alvin Lee; Hong Hong Huang; Palaniappan Sundaram; Keong Tatt Foo (Asian Journal of Urology)
Objective: Despite high-grade intravesical prostatic protrusion (IPP) being closely related to bladder outlet obstruction (BOO), up to 21% of patients with low IPP remain obstructed. This study evaluates the characteristics and urodynamic findings of men with small prostates and low IPP. Methods: One hundred and fourteen men aged >50 years old with lower urinary tract symptoms (LUTS) were assessed with symptoms, uroflowmetry, serum prostate-specific antigen (PSA), transabdominal ultrasound measurement of prostate volume (PV), IPP and post-void residual urine (PVRU). All patients underwent pressure flow studies. Patients with PV < 30 mL and IPP ≤ 10 mm were examined for parameters correlating with BOO or impaired detrusor contractility. Results: Thirty-six patients had PV < 30 mL and IPP <10 mm. Nine patients (25.0%) had urodynamic BOO, all with normal bladder contractility. Fourteen patients (38.9%) had poor detrusor contractility and all had no BOO. PV, PVRU and IPP were significantly associated with BOO, with IPP showing greatest positive correlation. Both Qmax and IPP were significantly associated with detrusor contractility. At 5-year follow-up, most patients responded to medical therapy. Only three out of nine patients (33.3%) with BOO eventually underwent surgery, and all had a high bladder neck seen on the resectoscope. Only one patient (7.1%) with poor detrusor contractility eventually required surgery after repeat pressure flow study revealed BOO. Conclusion: In men with small prostates and low IPP, the presence of BOO is associated with higher PV, PVRU and IPP, and most respond well to medical management. BOO can possibly be explained by elevation of the bladder neck by a small subcervical adenoma.